Comparing the impact of high versus low lockdown severity on the mental health of young people in Australia during the COVID-19 pandemic. (April 2023) - Meyer, Denny; Sumner, Philip J.; Tan, Eric J.; Neill, Erica; Hielscher, Emily; Blake, Julie A.; Scott, James G.; Phillipou, Andrea; Toh, Wei Lin; Van Rheenen, Tamsyn E.; Rossell, Susan L.
Highlights: Victoria, Australia had one of the most extended 2020 COVID-19 lockdowns in the world. But the mental health of young people in Victoria was no worse than in Queensland. Prior to the pandemic there was concern about negative emotion for young Australians. The high levels observed at the start of the pandemic have been maintained in Victoria. This makes the monitoring and addressing of youth mental health concerns a priority. Abstract: Young Australians have been differentially affected by lockdowns and social restrictions during the COVID-19 pandemic. This study compared the mental health impacts of the COVID-19 pandemic and associated restrictions for young people in two Australian states, Victoria and Queensland, with Victoria experiencing more days in lockdown and greater infection rates. An online survey was completed between 01/04/2021 and 31/07/2021 by 687 young people, aged 16 to 24 years; 337 from Victoria and 350 from Queensland. Levels of negative emotion feelings (as measured by the Depression Anxiety Stress Scale), and COVID-19 risk factors for negative emotions (such as financial hardship, education disruption, loneliness and household conflict), as well as protective factors (resilience and self-esteem) were compared between the Victorian and Queensland samples, also considering some early pandemic data and pre-pandemic norms. No significant differences in negative emotions were found between young people living in the two states, despite substantial differences in pandemic restrictions. The results indicated that young people in Queensland and Victoria had experienced similarly high levels of negative emotions, at levels also seen at the start of the pandemic in Victoria. This is of grave concern, requiring urgent attention as the pandemic continues.